Analisis User Experience Konten Spiral Abyss Challenge dari Video Game Genshin Impact menggunakan Game Experience Questionnaire (GEQ) - Giri Hartono; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
One of the most popular video games today is Genshin Impact. Currently the content of the endgame phase of this video game is the Spiral Abyss Challenge. Understanding the user experience (UX) of this endgame content is the key to being able to keep veteran players playing. Therefore, this research was conducted by analyzing the Spiral Abyss Challenge content from the video game Genshin Impact version 2.6 using the Game Experience Questionnaire (GEQ) in-game and post-game modules. This research aims to get an overview of the Spiral Abyss Challenge content UX and make recommendations to improve it. The research begins with problem identification, continues with literature study, research preparation, GEQ data collection, GEQ data analysis and ends with conclusions and suggestions. The author was assisted by 26 respondents to assess UX using the GEQ instrument. The results show that the Spiral Abyss Challenge content has a good UX. This is indicated by the high scores on the sensory and imaginative immersion components (2.79), positive affect (2.56), competence (2.52), challenge (2.63), and also the tension value (1.67) is low. Further UX improvement can be focused on the flow component which can be done by fulfilling several conditions, namely a balance of challenge difficulty with player abilities, clear goals, direct feedback and control.